Families Anarthruridae Lang, 1971, Colletteidae Larsen & Wilson, 2002, and Leptognathiidae Sieg, 1976* - Bird, Graham J. (Zootaxa, 2007)
The records of the tanaidomorphan family Anarthruridae, from the trenches and other Japanese waters are limited to three species of Anarthruridae, Anarthruropsis langi Kudinova-Pasternak, A. longa Kudinova-Pasternak and a new species of Siphonolabrum Lang. The abysso-hadal Siphonolabrum tenebrosus n.sp. that is described from this trench material is very similar to a shallow-water species, S. californiensis Dojiri & Sieg, from the Santa Barbara Channel, California. The heterogeneous family Colletteidae is represented by only three genera in records of tanaidaceans from Japanese waters, the Kurile-Kamchatka Trench and the Japan Trench, Collettea, Leptognathiopsis and Tumidochelia. New specimens of Leptognathia langi have allowed it to be partially redescribed and transferred to Leptognathiopsis. Recent changes in the taxonomy and classification of the Family Leptognathiidae are reflected in a much reduced list of species that are recorded from Japanese waters and the Kurile-Kamchatka/Japan Trench. All three genera, Biarticulata, Forcipatia and Leptognathia are represented, by six species. A new species of Leptognathia is described and a partial redescription is given of Forcipatia rotundicauda with the collection of new material.